Hubungan Antara Mindfulness dengan Kepuasan Hidup Mahasiswa Bimbingan dan Konseling - Waskito, Pranazabdian; Loekmono, J.T. Lobby; Dwikurnaningsih, Yari (Jurnal Kajian Bimbingan dan Konseling, 2018)
The research aimed at identifying the relation between mindfulness and life satisfaction among guidance and counseling students. The research was a correlational study using Kendall’s Tau-b correlation analysis technique. The respondents were 135 students from the Guidance and Counseling Study Program, Faculty of Teachers Training and Education, Universitas Kristen Satya Wacana. The data were gathered using the mindfulness scale and the life satisfaction scale. The results of the research showed that there had been positive and significant relationship between mindfulness and life satisfaction among the students of Guidance and Counseling Study Program, Faculty of Teachers Training and Education, Universitas Kristen Satya Wacana with the correlation coefficient rxy = 0.172 and p 0.007 (p < 0.01). The higher mindfulness score, the higher satisfaction score of life, and vice versa.